Sentiment, reason, and law : policing in the Republic of China on Taiwan - Martin, Jeffrey T. (Police/worlds. Studies in security, crime, and governance., 2019)
"The Republic of China on Taiwan spent nearly four decades as a single-party state under dictatorial rule (1949-1987) before transitioning to liberal democracy. This book describes the social life of a neighborhood police station during the first rotation in executive power following the democratic transition"--